2014
DOI: 10.3126/jkmc.v3i1.10918
|View full text |Cite
|
Sign up to set email alerts
|

Difficulty index in extraction of impacted mandibular third molars and their post-operative complications

Abstract: Background: Although the removal of impacted mandibular third molars is a common minor oral surgical procedure, the extraction of these teeth can present with certain post-operative complications. Koerner KR proposed a Diffi culty Index Scale for removal of these teeth on the basis of local anatomy and radiographs, which were helpful in predicting the diffi culty that would be encountered intra-operatively, as well as the post-operative complications. Objective: To study the different post-operative complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 11 publications
(17 reference statements)
1
20
0
Order By: Relevance
“…In this study, higher incidence of mandibular third molar impaction was found in females (54.2%) which is corroborated by studies done by Upadhyaya et al 18 and Khanal et al 19 This can be attributed to differences in growth pattern between males and females. Females have less incremental and a shortened duration for growth of mandible compared to males.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, higher incidence of mandibular third molar impaction was found in females (54.2%) which is corroborated by studies done by Upadhyaya et al 18 and Khanal et al 19 This can be attributed to differences in growth pattern between males and females. Females have less incremental and a shortened duration for growth of mandible compared to males.…”
Section: Discussionsupporting
confidence: 90%
“…Several authors have mentioned similar observation. 18,19 Pus discharge was found statistically insignificant between the two study groups. Data from this study showed the incidence of infection at 5% in POD 1 and 1.7% in POD 3 for Amoxicillin group and nil for Azithromycin group.…”
Section: Discussionmentioning
confidence: 67%
“…Studies found that the difficulty in L3M extraction is directly associated with vertical and horizontal tooth position [3,17,18], and with bulbous roots [3,18].…”
Section: Discussionmentioning
confidence: 99%
“…When tooth angulation take in account, more postoperative complication were associated with distoangular, vertical [17,19], and mesioangular impaction [20]. The position of the L3M relative to the inferior alveolar nerve was also associated with an increased risk for complications [20].…”
Section: Discussionmentioning
confidence: 99%
“…8 The difficulty index consist of three components; Angulation (in relation to long axis of second molar [mesioangular, distoangular, horizontal], Depth (in relation to occlusal plane [Class A,B,C]) and position (in relation to vertical ascending ramus [Class I,II & III]). 9 The occurrence of these indices are associated with several factors which include age, gender, and general health of patient, the smoking status, use of oral contraceptive (in case of females), and surgical technique used along with the preferred flap design. 10 The aim of this study is to evaluate the less aggressive technique Ward's versus Modified Ward's flap with respect to less post-operative complications in removal of lower third molar.…”
Section: Introductionmentioning
confidence: 99%